Clinical significance of 206 station lymph node in transverse colon cancer. (18th April 2022) - Xu, Yu Xin; Huang, Ying; Wang, Xiao Jie; Ye, Dao Xiong; Chi, Pan
Abstract: Background: Lymph node (LN) metastasis is crucial in determining the prognosis and treatment options for colon cancer patients. Our work was to study whether the lymph nodes beyond D3 station in transverse colon cancer, especially 206 LN, should be dissected. Methods: A total of 225 patients within our department were reviewed. The primary and secondary endpoints were overall survival (OS) and disease‐free survival (DFS). We employed Propensity score weighting (PSW) for weighing participants to balance observed confounders between the 206 D+ group and the 206 D− group. Results: The rate of metastasis in station 206 was 9.3%. Only T stage (OR, 3.009; 95% CI, 1.018–8.892), N stage (OR, 9.818; 95% CI, 1.158–83.227), and M stage (OR, 26.126; 95% CI, 1.274–535.945) were an independent risk factor for 206 station metastasis in multivariate logistic analysis. The 206 D+ group had a similarly survival than the 206 D− group (3‐year DFS, 89.6% v 85.9%; p  = 0.389; 3‐year OS, 94.6% v 85.3% p  = 0.989). PSW further verified it. Metastasis of 206 station LN is not an independent prognostic factor, but a predictive factor of DFS. Conclusion: Station 206 LN positive is a predictive factor for DFS. Only the patient with T1‐3, N+ who is at a high risk of 206 station LN metastases should consider dissecting 206 station LN. Abstract : Two outcomes of the analysis are (a) station 206 LN positive is a predictive factor for DFS. (b) dissection of the 206 LN station seems to have a similar OS and DFS as compared with those who did not undergo this dissection. There might be due to adjuvant chemotherapy. Only the patient with T1‐3, N+ who is a high risk of 206 station LN metastases consider dissecting 206 station LN. The topic we cover is of interest and relevance to the clinical decision of 206 LNs dissection.